Hematological and gastrointestinal protection effects of ginger rhizome on whole-body exposure of gamma radiation in mice1 - Gargouma, Huda; Elramlya, Tamer; Elmahjooba, Sana; Elgalib, Maha; El faitori, Hussain (Libyan Journal of Science &Technology, 2022)
Radiation can induce acute radiation sickness in different ways. In this study, we investigated the radio-protective efficacy of ginger extract (GE) against the gamma (γ) ray-induced damage on mice. The source of gamma radiation was cobalt 60 (Co-60). GE was administered to mice at a dose of 5 ml/kg intraperitoneally (IP) for 5 consecutive days before exposing them to 8 Gray (Gy) (unit of ionizing radiation dose) of Co-60-gamma-radiation. Mice treated with GE before irradiation (pretreated group) showed a significant decrease in the mortality of lethally irradiated mice. Moreover, spleen weight was significantly increased. Besides, the GE treat- ment facilitated the recovery of white blood cells (WBC), and hemoglobin (HGB) cell number. Altogether, the findings indicated that ginger has remarkable effects on mice against hemato- poietic suppression and gastrointestinal damage caused by irradiation.